Influence of biologically active preparations on biochemical indicators of sows’ blood and the survival level of sucking pigs - Zakharchenko, K.; Khomenko, M.; Seba, M.; Golovetskyi, I.; Trokhymenko, V.; Bryukhachova, I. (Diponegoro University, 2024)
The analysis of the influence of biologically active preparations on the biochemical status of the body of sows is given in the article. Nanoaquachelate of Ge (G18Ge and G9Ge groups) and Quatronan-Se (Q-Se group) were used 4 days before and 10 days after farrowing, Glutam 1M was used 3 days after the farrowing (GM1, G18Ge and G9Ge groups). Based on the results obtained, it has been found that use of preparations in the period from 4 days after the farrowing to weaning contributes to lower cholesterol level in the G18Ge, G9Ge and Q-Se groups by 21.7%, 29.2 % and 33.3%, respectively. Also, significant changes have been observed in the in the concentration of protein, in all groups to which the studied drugs were administered before weaning it tended to decrease by 9.9; 7.6; 6.6 and 6.3%, respectively, while in the group C (control) the difference was only 1.6%. In addition, a study of the influence of preparations on the body of piglets through sow milk shows that the level of piglets’ survival in the GM1, G18Ge, G9Ge and Q-Se groups was higher than in the C group. The highest sur-vival has been observed in the G18Ge group and on the day of weaning was 90.2%.